Chemo-thermo-viscoelastic characterization and material modeling of electronic packaging moulding compound materials - Neo, Raynard Guan Hock (2008)
Highly filled epoxy moulding compounds are widely used for the encapsulation of microelectronic chips today. As thermo-rheological behaviour of these thermosetting materials is complex, the material characteristics must be determined by experiments and described by mathematical models so that a better understanding can be obtained. With the knowledge of the cure behaviour and changes in rheological properties as a result of cure, the optimum processing conditions for transfer moulding can be determined. On the other hand, if the effective mechanical and thermal expansion properties of the moulding compound can be determined with the aid of the constituent properties, the desired material properties can be designed without time-consuming reproductions of experimentation. Thermo mechanical properties of the material can be determined using differential scanning calorimetry, dynamic mechanical spectrometers, thermal mechanical analysers and dynamic mechanical thermal analysers.